Factors influencing the impact of oral health on the daily activities of adolescents, adults and older adults - Jaqueline Vilela Bulgareli; Eduardo Tanajura de Faria; Karine Laura Cortellazzi; Luciane Miranda Guerra; Marcelo de Castro Meneghim; Glaucia Maria Bovi Ambrosano; Antonio Carlos Frias; Antonio Carlos Pereira (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE: Analyze if clinical, sociodemographic and access to dental services variables influence the impact of oral health on the daily activities of adolescents, adults and older adults. METHODS: A cross-sectional study with secondary data from the State Oral Health Survey (SB São Paulo 2015) conducted in 163 cities of São Paulo. A total of 17,560 individuals from three age groups: 15-19-year-old (n = 5,558), 35-44-year-old (n = 6,051), and older people of 65 years or more (n = 5,951) participated in the survey. The selection was made by probabilistic sample by conglomerates in two stages. The endpoint variable was the impact of oral health on daily activities, evaluated by the Oral Impacts on Daily Performances questionnaire, containing questions about eating, talking, oral hygiene, relaxation, sports practice, smile, study or work, social contact, and sleep. Oral Impacts on Daily Performances was dichotomized with and without impact. The independent variables were sociodemographic, clinical and access variables, divided into three blocks. A hierarchical multiple logistic regression analysis was performed considering the complex sampling plan of clusters. Each observation received a specific weight, depending on the location that resulted in weighted frequencies and adjusted for the design effect. RESULTS: The presence of oral health impact was observed in 27.9% of the individuals. In block 1, female gender and black/brown ethnic group had a greater chance of impact of oral health on quality of life, as well as the adults and the older adults in relation to adolescents. In block 2, family income up to R$1,500 was associated with the presence of impact. In block 3, individuals who reported toothache, used the public service and sought dental treatment had a greater chance of impact. CONCLUSIONS: Sociodemographic, clinical and access to health services variables influence the impact of oral health on the daily activities of adolescents, adults and older adults.